Aquatic insects decline in abundance and occupy low‐quality artificial habitats to survive hydrological droughts. (27th June 2019) - Deacon, Charl; Samways, Michael J.; Pryke, James S.
Abstract: Hydrological extremes have negative impacts on natural, agricultural, and urban landscapes and place substantial ecological pressure on freshwater habitats. However, the role of artificial freshwater habitats during hydrological drought is poorly understood. Insects make up much of total aquatic fauna and lend themselves to understanding how drought impacts freshwater ecosystems. Using the Greater Cape Floristic Region as an example of a drought‐prone area, we determined the effects of a severe drought on a subset of insects occupying lentic habitats in terms of their species richness, diversity, and assemblage composition. Here, we: (1) calculated the percentage change in average precipitation between a record dry season and the last consistently wet decade; (2) identified the environmental variables driving aquatic insect species richness, diversity and composition; (3) identified the environmental differences between natural ponds and artificial reservoirs; (4) determined whether artificial reservoirs act as suitable habitats for focal taxa during drought; and (5) compared these results to other, pre‐drought studies. Environmental variables related to water chemistry and physical characteristics were drivers of species richness, diversity, and composition, yet vegetation cover remained a major driver. In terms of marginal vegetation cover, most artificial reservoirs did not resemble natural ponds, yet overall 38.4% of sampled aquatic insect species were shared between natural ponds and artificial reservoirs. We found some rare endemic species in artificial reservoirs that had never before been recorded in this habitat during wet years. When our drought findings were compared to earlier, wet years, species richness did not change significantly, although abundance was much lower during the drought year. We postulate that historically, these aquatic insects, which have been through many ecological filters such as drought, must have sought low‐quality habitats to survive water stress periods. Artificial reservoirs, being novel landscape features, cannot fully replace natural ponds, but enable some aquatic insects to survive drought. Artificial reservoirs can be attractive habitats to aquatic insects when they resemble natural ponds, with specific reference to their marginal vegetation characteristics.